Study guides

Q: X2 -2x plus 65 equals 0?

Write your answer...

Submit

Related questions

x2 + 2x - 15 = (x - 3)(x + 5)

The vertex is at (-1,0).

If you have an equation of x2 plus x2, it is the same as saying 2 times x plus 2 times x. This can be written as 2x + 2x or x2 + x2. It is the same, then, as 4x. For example, if x equals 5: 2(5) + 2(5) = 10 + 10 = 20. 20 also equals 4(5).

2x = x2 + 4x - 3 x2 + 2x - 3 = 0 (x - 1)(x - 2) = 0

x2 + 2x -6 = 0 x2 + 2x + 1 = 7 (x + 1)2 = 7 x = -1 ± √7

(2x)ysquared

x2 + 2x = 3 x2 + 2x - 3 = 0 (x + 3)(x - 1) = 0 x ∈ {-3, 1}

x2+10x+1 = -12+2x x2+10x-2x+1+12 = 0 x2+8x+13 = 0 Solving by using the quadratic equation formula: x = - 4 - or + the square root of 3

The answer is (3.5)2 plus (4)2 equals 410.

4X + 2x = 1. Where x = 0.166666666666666666666666666666666666666 recurring.

x2 - 10x - 6 = 2x + 1 Subtracting 2x + 1 from both sides gives: x2 - 12x - 7 = 0

No real roots

x2+10x+1 = -12+2x x2+8x+13 = 0 The solution: x = -4 + the square root of 3 or x = -4 - the square root of 3

y2 - 5y + 2x - x2 - 120 is not a circle. It is a hyperbola rotated through 90 degrees.

It depends what x equals, unless you know that it's impossible to answer the question past "2x + 4"

-x2 + 2x + 48 = (-x - 6)(x - 8)

None because the discriminant is less than zero

2x^2 + 8x + 3 = 0

x2-2x-15 = (x+3)(x-5) when factored

If: x2+2x-3 = 0 Then: x = 1 or x = -3

x3 - x2 + 2x = x*(x2 - x + 2) which cannot be factored further.

x2 + 2x - 15 = (x + 5)(x - 3)

(x - 7)(x + 9) = x2 + 2x - 63

-x2 + 2x + 48 = (x +6)(8 - x)

If we assume that it equals zero and you wish to solve for x, then the answer is:-x2 + 2x - 3 = 0x2 - 2x + 3 = 0x2 -2x + 1 = -2(x - 1)2 = -2x - 1 = ± √(-2)x = 1 ± i√2